The effect of perception of benefits, ease of use, trust on the decision to use QRIS with attitude as an intervening variable - rouw, delicia kezia; Nugrahaningrum, Kristi Febi; Edy Raharja (Proceeding of International Management Conference and Progressive Papers, 2024)
The purpose of this study is to empirically test the effect of perceived benefits on attitudes towards using QRIS. To empirically test the effect of ease of use on attitudes towards using QRIS. To empirically test the effect of trust on attitudes towards using QRIS. To empirically test the effect of attitudes towards decisions to use QRIS. To empirically test the effect of perceived benefits on decisions to use QRIS with attitudes as intervening variables. The method used in this study is quantitative. Questionnaires are used in collecting research data. The population in this study were all MSMEs that have used QRIS. The minimum sample is 160 respondents, so this study used 160 respondents, namely MSMEs in the city of Semarang who have used QRIS for at least 3 months. This study uses an analysis technique, namely Partial Least Square (PLS) to analyze the data.